2019
DOI: 10.37630/jpm.v9i1.180
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Perangkat Pembelajaran Model PBL Berbasis STEM untuk Melatih Keterampilan Berfikir Kreatif Siswa Tuna Netra

Abstract: Tujuan penelitian ini adalah untuk mengembangkan perangkat pembelajaran berbasis STEM dan mempermudah guru dalam menyampaikan materi dan memberikan pemahaman sekaligus melatih keterampilan berikir kreatif siswa tuna netra. Selain dari itu mempermudah guru dalam menyampaikan materi yang abstrak kepada siswa tuna netra. Penelitian ini menggunakan penelitian R &D (Research and Development). Instrumen yang diguakan dalam penelitian ini adalah Lembar keterlaksanaan RPP, Lembar Pegamatan Aktivitas Siswa, Lembar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Other research results reveal that the STEM-based problem-based learning model increases students' critical thinking abilities (Mustofa et al, 2021). Further research revealed that STEM-based PBL model learning tools effectively trained blind students' creative thinking skills (Sarnita et al, 2019). Based on several research results, it can be said that the STEM-based PBL model can significantly positively influence students' thinking abilities.…”
Section: Discussionmentioning
confidence: 94%
“…Other research results reveal that the STEM-based problem-based learning model increases students' critical thinking abilities (Mustofa et al, 2021). Further research revealed that STEM-based PBL model learning tools effectively trained blind students' creative thinking skills (Sarnita et al, 2019). Based on several research results, it can be said that the STEM-based PBL model can significantly positively influence students' thinking abilities.…”
Section: Discussionmentioning
confidence: 94%
“…Creative thinking is the most important part of the 4.0 industrial revolution era. Therefore, creative thinking skills must be trained as early as possible, so visually impaired students can compete in industry and society [14]. The challenges of a rapidly changing world require innovative ideas and approaches.…”
Section: Resultsmentioning
confidence: 99%
“…Alat peraga berfungsi untuk mempermudah guru dalam menyampaikan materi pembelajaran sehingga diharapkan dapat mencapai kompetensi pembelajaran. Media pembelajaran yang digunakan oleh guru dapat dijadikan sebagai ruang bagi siswa dalam melakukan eksperimen, siswa menjadi lebih aktif dalam belajar, mengemukakan pendapat atau memberikan ide-ide kretaif, mencoba hal-hal baru yang belum pernah dilakukan sebelumnya (Fitria Sarnita, Ainun Fitriani, and Widia 2019). Media pembelajar inovatif juga berpengaruh terhadap kreativitas sehingga berdampak pada hasil belajar siswa (Silaban and Napitupulun 2011).…”
Section: Hasil Dan Pembahasanunclassified